2020
DOI: 10.4317/jced.56989
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-heating on monomer elution from bulk-fill resin composites

Abstract: Background The present study was aimed to evaluate the effect of pre-heating of bulk -fill resin composites on monomer elution from them. Material and Methods Three different types of resin composites were used including Tetric N-Ceram Bulk Fill, X-tra Fill and X-tra Base. 10 cylindrical samples were prepared from each resin composites. Before light curing, 5 samples were pre-heated until reaching 68˚C, then 5 other samples were polymerized at room temperature. After 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, only one published article deals with the monomer elution from three pre-heated RBCs and found no effect of pre-cure temperature (68 °C) on the amount of leached UDMA, TEGDMA, and BisGMA [ 85 ]. Few available pieces of research reported that pre-heating of both conventional and bulk-fill RBCs did not influence cell viability, however, polymerized samples were used to examine the cytotoxicity without determination of the eluted monomers [ 63 , 83 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one published article deals with the monomer elution from three pre-heated RBCs and found no effect of pre-cure temperature (68 °C) on the amount of leached UDMA, TEGDMA, and BisGMA [ 85 ]. Few available pieces of research reported that pre-heating of both conventional and bulk-fill RBCs did not influence cell viability, however, polymerized samples were used to examine the cytotoxicity without determination of the eluted monomers [ 63 , 83 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many elution studies in the literature. These investigate, for example, the influence of additives [27], exposure time to light [28] or thermal pre-treatment on the amount of elutable substances [29]. Their focus is on the development of new conditions that occur in the care of patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, SF has the higher filler content (83.5%), and this could be the main reason why SF with the lowest DC value had the lowest total amount of eluted monomers. An increase in filler content leads to a decrease in the solvent absorption of composites, thus reducing the degree of monomer elution [32]. Khalid et al showed that significantly high monomer elution and structural changes occurred at SDR [33].…”
Section: Discussionmentioning
confidence: 99%